The role of quality management system in the development of Kuban SAU human capital - YU. P. Fedulov; A. V. Zagorulko; I. T. Zaika; V. M. Smolentsev (Высшее образование в России)
The article shows the experience of Kuban State Agrarian University in development andimplementation of the quality management system. An approved approach to evaluation of the effectiveness of QMS improvement describing the dynamics of university development is presented.